1985
DOI: 10.21273/jashs.110.3.333
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CO2 on Cinnamic Acid-4-Hydroxylase in Relation to Phenolic Metabolism in Lettuce Tissue

Abstract: An atmosphere of air + 15% CO2 prevented the development of cinnamic acid-4-hydroxylase in both lettuce (Lactuca sativa L.) and potato (Solanum tuberosum L.) tissues. Subsequent removal of CO2 did not allow the enzyme development to proceed, whereas total phenolic content increased and browning became visible. In addition, CO2 did not have an inhibitory effect on the enzyme, prepared from potato tissue, per se. Thus, the effects of CO2 on inhibition of lettuce tissue browning does not appear to involve this en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A step either preceding or following PAL induction was probably inhibited or not induced under high C 0 2 and, therefore, phenolic production was inhibited. Siriphanich and Kader (1985b) found that 15% C 0 2 prevented the increase in cinnamate 4-hydroxylase activity. However, subsequent removal of C 0 2 did not result in an increase of this enzyme activity, whereas total phenolic content did increase.…”
Section: Discussionmentioning
confidence: 94%
“…A step either preceding or following PAL induction was probably inhibited or not induced under high C 0 2 and, therefore, phenolic production was inhibited. Siriphanich and Kader (1985b) found that 15% C 0 2 prevented the increase in cinnamate 4-hydroxylase activity. However, subsequent removal of C 0 2 did not result in an increase of this enzyme activity, whereas total phenolic content did increase.…”
Section: Discussionmentioning
confidence: 94%
“…Polyphenol oxidase (PPO) activity was determined by evaluating catechol oxidation at 420 nm after adding 10 mM KPO 4 (pH 7.0) and 20 mM catechol. The absorbance change per min was set at one unit (Siriphanich & Kader, 1985). Phenylalanine ammonia‐lyase (PAL) activity was assayed by monitoring phenylalanine oxidation at 290 nm after reacting with 1 mM 2‐mercaptoethanol, 100 mM Tris–HCl, and 15 mM L‐phenylalanine.…”
Section: Methodsmentioning
confidence: 99%
“…The activity of defense enzymes such as catalase (CAT) was measured by using the Aebi et al [33] technique and peroxidase (POD) activity was measured as per the guaiacol oxidation technique [34]. A modified version of Siriphanich and Kader's [35] procedure was used to determine the polyphenol oxidase (PPO) activity. The Godwin et al [36] approach was used to measure phenylalanine ammonia-lyase (PAL).…”
Section: Estimation Of Enzyme Activity and Chlorophyll Contentmentioning
confidence: 99%